Resolution of Neonatal Hypertrophic Cardiomyopathy Presumed Secondary to Acquired Maternal Ribonucleoprotein and Smith Autoantibodies - Shah, A.; Winrow, A.; Fulljames, R.; Naqvi, N.; Bansal, R. A.; Bansal, A. S. (American Journal of Perinatology Reports, 2013)
Severe asymmetrical hypertrophic cardiomyopathy without heart block accompanied by neuromuscular hypotonia and feeding difficulties was evident shortly after birth in the second child of a mother with systemic lupus erythematosus who had no indication of gestational diabetes. High-level anti-ribonucleoprotein (RNP) and Smoth (Sm) antibodies arising from transplacental transfer of maternal antibodies were detected in the child's serum. The cardiac abnormalities improved with a commensurate decline in antibody titers. Previously reported cases of neonatal cardiomyopathy with endocardial fibroelastosis have been ascribed to the transplacental transfer of maternal Sjogrens Syndrome (SS) A (Ro) and Sjogrens Syndrome (SS) B (La) antibodies and have been more severe and persistent compared with our patient. We advocate close monitoring of all babies of mothers with systemic autoimmunity for changes in heart rate during pregnancy and signs of heart failure and neuromuscular weakness after delivery.
Keywords: hypertrophic cardiomyopathy; neonatal; lupus; anti-RNP and anti-Sm antibodies; maternal transmission